Assistance in Building Positive Character in Social Media for Orphanage Children - Adji, Riyanto; Situmorang, Alvin Yosafat; Asiari, Dirsanti Nur Apriliani; Mahendra, Gilang Riza; Makmuria, Ignaz Fico; Wijaya, Ricko Aryasena; Liswandi, Liswandi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Children are a golden age in their growth, so that various information that comes in both verbally and visually will be recorded well, therefore children aged 2-13 years need to receive assistance and supervision over all their activities. Since the COVID-19 pandemic hit the world, all learning activities have changed to online learning, as a result of online learning, there has been a change in children's attitudes. This change is due to children accessing social media a lot and receiving less guidance from their parents, resulting in excessive use of social media. For children and teenagers who have parents, monitoring will be possible, but for children and teenagers in orphanages, do they receive monitoring, assistance, and supervision from parents? Therefore, in this community service activity, the researcher wanted to know more about monitoring the use of social media by children in orphanages. Several games were carried out to determine the extent of children's use of social media, and as a result, the games could divert children's tendencies to use social media.